APLIKASI PERENCANAAN STRATEGIS SISTEM INFORMASI MENGGUNAKAN FRAMEWORK WARD DAN PEPPARD PADA PT KODING NEXT INDONESIA - Nata Nael; Elis Sondang Dasawati (Institut Bisnis dan Informatika Kwik Kian Gie, 2020)
Koding Next Indonesia is a company engaged in the field of programming courses. To get competitive m advantage a company must have a good strategic planning. Broadly speaking, this study aims to design an information system strategic planning along with a recommended application portfolio and to produce applications that can help Koding Next Indonesia in conducting strategic planning in the future. The framework used in conducting information systems strategic planning is the Ward and Peppard framework. In conducting data analysis methods used include SWOT Analysis, Value Chain Analysis and Five Forces Analysis used for analysis of internal and external business environments. The McFarlan portfolio is used to map application portfolios that currently exist and to map application recommendations. In the end, this research resulted in an information system strategy and application portfolio that will support the company in achieving its stated goals and produce an application that can help companies carry out strategic information systems planning in the future. Kata Kunci— Perencanaan Strategis Sistem Informasi, Ward and Peppard Model, Analisis SWOT, Analisis Five Forces, Analisis Value Chain